2012
DOI: 10.1093/carcin/bgs396
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan induces changes in the epithelial to mesenchymal transition and decreases metastasis by enhancing ubiquitin-dependent TGF  receptor degradation in breast cancer

Abstract: Fucoidan, a polysaccharide extracted from brown seaweeds, reduces tumor cell proliferation. Fucoidan inhibits the growth of breast cancer cells such as 4T1 and MDA-MB-231 and decreases their cell colony formation. Moreover, fucoidan reduces metastatic lung nodules in 4T1 xenograft female Balb/c mice. The molecular network of transforming growth factor β (TGFβ) receptors (TGFRs) plays an important role in the regulation of the epithelial to mesenchymal transition (EMT) in cancer cells. Using 4T1 and MDA-MB-231 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 42 publications
5
97
0
10
Order By: Relevance
“…Recently, several studies suggested that fucoidan could inhibit EMT in various cell types. For instance, Hsu et al found that fucoidan could regulate EMT by modulating TGFR/Smad signaling, which leads to the inhibition of breast cancer metastasis in vitro and in vivo [34]. Yan et al found that fucoidan regulates the miR-29b/DNMT3B/MTSS1 axis and inhibits EMT in human hepatocellular carcinoma cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies suggested that fucoidan could inhibit EMT in various cell types. For instance, Hsu et al found that fucoidan could regulate EMT by modulating TGFR/Smad signaling, which leads to the inhibition of breast cancer metastasis in vitro and in vivo [34]. Yan et al found that fucoidan regulates the miR-29b/DNMT3B/MTSS1 axis and inhibits EMT in human hepatocellular carcinoma cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of biological activities of fucoidan varies with species, molecular weight, composition, structure and the route of extraction (Fitton 2011), and its non-animal origin brings particular pharmacological activities (Senni et al 2006). Fucoidan has been well studied for its antitumor (Hsu et al 2013), antiviral (Tengdelius et al 2014), anti-inflammatory (Hwang et al 2011), and anticoagulant (Irhimeh et al 2009) activities. These biological activities are closely related to fucoidan's molecular weight (Yang et al 2008) and sulfate content (Soeda et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…transforming growth factor β receptor 1/2, TGF-βR1/2), co z kolei przyczynia się do ograniczenia zdolności migracji i inwazji okolicznych tkanek. Ponadto udowodniono, że spadek ekspresji TGFR wynika z jego wzmożonej ubikwityno-zależnej degradacji w proteasomie [50]. Powyższe efekty obserwowano zarówno w warunkach in vivo, jak i in vitro [50].…”
Section: Przerzutowanieunclassified
“…Ponadto udowodniono, że spadek ekspresji TGFR wynika z jego wzmożonej ubikwityno-zależnej degradacji w proteasomie [50]. Powyższe efekty obserwowano zarówno w warunkach in vivo, jak i in vitro [50]. Kolejne badanie oceniające skuteczność fukoidyny w hamowaniu przerzutowania zostało przeprowadzone przez Huanga i wsp.…”
Section: Przerzutowanieunclassified